2016
DOI: 10.1002/2016gl069973
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the impact of storms on sustaining summer primary productivity in the Sub‐Antarctic Ocean

Abstract: In the Sub‐Antarctic Ocean elevated phytoplankton biomass persists through summer at a time when productivity is expected to be low due to iron limitation. Biological iron recycling has been shown to support summer biomass. In addition, we investigate an iron supply mechanism previously unaccounted for in iron budget studies. Using a 1‐D biogeochemical model, we show how storm‐driven mixing provides relief from phytoplankton iron limitation through the entrainment of iron beneath the productive layer. This eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 43 publications
(67 reference statements)
3
57
0
Order By: Relevance
“…However, there is now compelling evidence to suggest that storm events may also play a critical role in extending the duration of summertime production through intra-seasonal entrainment of dissolved iron from a subsurface reservoir (Carranza and Gille, 2015;Fauchereau et al, 2011;Swart et al, 2015;Thomalla et al, 2011). This mechanism was tested using a 1-D biogeochemical model by Nicholson et al (2016) whose results suggest that intra-seasonal mixed-layer perturbations may offer relief from iron limitation in summer, particularly if there is sufficient subsurface vertical mixing beneath the surface mixed layer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there is now compelling evidence to suggest that storm events may also play a critical role in extending the duration of summertime production through intra-seasonal entrainment of dissolved iron from a subsurface reservoir (Carranza and Gille, 2015;Fauchereau et al, 2011;Swart et al, 2015;Thomalla et al, 2011). This mechanism was tested using a 1-D biogeochemical model by Nicholson et al (2016) whose results suggest that intra-seasonal mixed-layer perturbations may offer relief from iron limitation in summer, particularly if there is sufficient subsurface vertical mixing beneath the surface mixed layer.…”
Section: Discussionmentioning
confidence: 99%
“…Tagliabue et al (2014) postulated that due to weak diapycnal inputs of iron, there must be a heavy reliance on Fe recycling within the mixed layer to meet the iron demand. An alternative hypothesis is that summer storms can sustain mixed-layer biomass through the entrainment of limiting nutrients, particularly in the SAZ (Carranza and Gille, 2015;Nicholson et al, 2016;Swart et al, 2015). As a storm passes through the SAZ, it deepens the mixed layer accessing the subsurface iron reservoir; the subsequent re-shoaling of this buoyant water fuels surface water phytoplankton growth in a high-light and replenished-nutrient environment.…”
Section: T J Ryan-keogh Et Al: Seasonal Development Of Iron Limitamentioning
confidence: 99%
See 2 more Smart Citations
“…Weak diapycnal inputs and a heavy reliance on iron recycling was suggested by Tagliabue et al (2014) to match approximate phytoplankton utilization within the pelagic zones. An alternative theory that postulates the importance of summer storms may also be pivotal in understanding the seasonal dynamics of phytoplankton primary productivity (Nicholson et al, 2016;Swart et al, 2015;Thomalla et al, 2015), with respect to the sustained bloom observed in the sub-Antarctic Zone (SAZ). Here, summer storms are said to periodically deepen the mixed layer to below the ferricline followed by rapid shoaling during quiescent periods that balances the supply of light and iron in the upper oceans favouring phytoplankton growth that culminates in a sustained summer bloom .…”
Section: Introductionmentioning
confidence: 99%